Isolation, characterization and efficacy of phage MJ2 against biofilm forming multi-drug resistant Enterobacter cloacae - Jamal, Muhsin; Andleeb, Saadia; Jalil, Fazal; Imran, Muhammad; Nawaz, Muhammad Asif; Hussain, Tahir; Ali, Muhammad; Ur Rahman, Sadeeq; Das, Chythanya Rajanna (Folia microbiologica, 2019)
Biofilm is involved in a variety of infections, playing a critical role in the chronicity of infections. Enterobacter cloacae is a biofilm-forming and multi-drug-resistant (MDR) nosocomial pathogen leading to significant morbidity and mortality. This study aimed at isolation of a bacteriophage against MDR clinical strain of E. cloacae and its efficacy against bacterial planktonic cells and biofilm. A bacteriophage MJ2 was successfully isolated from wastewater and was characterized. The phage exhibited a wide range of thermal and pH stability and demonstrated considerable adsorption to host bacteria in the presence of CaCl2 or MgCl2. Transmission electron microscopy (TEM) showed MJ2 head as approximately 62 and 54 nm width and length, respectively. It had a short non-contractile tail and was characterized as a member of the family Podoviridae [order Caudovirales]. The phage MJ2 was found to possess 11 structural proteins (12-150 kDa) and a double-stranded DNA genome with an approximate size of 40 kb. The log-phase growth of E. cloacae both in biofilm and suspension was significantly reduced by the phage. The E. cloacae biofilm was formed under different conditions to evaluate the efficacy of MJ2 phage. Variable reduction pattern of E. cloacae biofilm was observed while treating it for 4 h with MJ2, i.e., biofilm under static conditions. The renewed media with intervals of 24, 72, and 120 h showed biomass decline of 2.8-, 3-, and 3.5-log, respectively. Whereas, the bacterial biofilm formed with dynamic conditions with refreshing media after 24, 72, and 120 h demonstrated decline in growth at 2.5-, 2.6-, and 3.3-log, respectively. It was, therefore, concluded that phage MJ2 possessed considerable inhibitory effects on MDR E. cloacae both in planktonic and biofilm forms.
Keywords: Host Specificity; Genome Size; Podoviridae; Enterobacter cloacae; mnohočetná bakteriální léková rezistence; přichycení viru; Temperature; mikrobiální viabilita; Viral Proteins; molekulová hmotnost; genom virový; teplota; Microbial Viability; Drug Resistance, Multiple, Bacterial; chlorid hořečnatý; Wastewater; hostitelská specificita; Virus Attachment; virové proteiny; Genome, Viral; biofilmy; délka genomu; DNA virů; Hydrogen-Ion Concentration; DNA, Viral; Magnesium Chloride; chlorid vápenatý; odpadní voda; Calcium Chloride; koncentrace vodíkových iontů; Biofilms; Molecular Weight